Targeted Therapy Followed by Salvage Surgery and Adjuvant Therapy: A Promising Therapy for Lung Cancer With Malignant Pleural Effusion From a Case Report - Deng, Han-Yu; Li, Deyan; Ren, Ying; Wang, Ke; Tang, Xiaojun (Frontiers in Surgery, 2021)
Introduction: Malignant pleural effusion (MPE) was encountered in about 8%-15% of lung cancer patients at initial cancer diagnosis. The optimal therapeutic strategies for lung cancer with MPE remains unclear. Case Description: Here we reported a case of lung cancer with MPE, who was successfully managed with multidisciplinary therapeutic strategy. The patient initially received gefitinib for 4 months with excellent response and he underwent salvage thoracoscopic lobectomy and systematic lymphadenectomy. Pathological complete response was confirmed for the patient and he discontinued gefitinib but received 4 cycles of adjuvant chemotherapy instead. The patient is still alive without disease progression for 51 months after surgery. Conclusions: Combining targeted therapy, salvage surgery, and adjuvant therapy may be a promising treatment strategy for lung cancer with MPE harboring oncogene-targeted mutations.